2008
DOI: 10.1073/pnas.0709372104
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for declines in human population densities during the early Upper Paleolithic in western Europe

Abstract: In western Europe, the Middle to Upper Paleolithic (M/UP) transition, dated between Ϸ35,000 and Ϸ40,000 radiocarbon years, corresponded to a period of major human biological and cultural changes. However, information on human population densities is scarce for that period. New faunal data from the high-resolution record of Saint-Cé saire, France, indicate an episode of significant climatic deterioration during the early Upper Paleolithic (EUP), which also was associated with a reduction in mammalian species di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 31 publications
1
42
1
1
Order By: Relevance
“…In addition, the summed probability distribution frequencies of the calibrated radiocarbon dates decline steeply simultaneously with a similar decline in the reindeer population in the region at the Older Dryas/GI-1d transition (Aaris-Sørensen et al 2007) (Figure 8). Morin (2008) has recently shown that Rangifer herd sizes in historical times fl uctuated in largely unpredictable cycles and that the fl uctuations were Although these values may not be directly comparable to those plotted in Figure 1, faunal diversity is shown to significantly decline with latitude (r s 0.56, p  0.01), despite the large climatic fl uctuations spanned by these sites. The extremely low diversity values in the northernmost sites are noteworthy.…”
Section: Case Study 3: Demography Social Relations and Biosocial Comentioning
confidence: 92%
See 3 more Smart Citations
“…In addition, the summed probability distribution frequencies of the calibrated radiocarbon dates decline steeply simultaneously with a similar decline in the reindeer population in the region at the Older Dryas/GI-1d transition (Aaris-Sørensen et al 2007) (Figure 8). Morin (2008) has recently shown that Rangifer herd sizes in historical times fl uctuated in largely unpredictable cycles and that the fl uctuations were Although these values may not be directly comparable to those plotted in Figure 1, faunal diversity is shown to significantly decline with latitude (r s 0.56, p  0.01), despite the large climatic fl uctuations spanned by these sites. The extremely low diversity values in the northernmost sites are noteworthy.…”
Section: Case Study 3: Demography Social Relations and Biosocial Comentioning
confidence: 92%
“…Although a lack of quantitative demographic data for these forager groups makes the link between prey herd size and human population densities ultimately dependent on oral and anecdotal histories, reasonable quantitative demographic data on other high-latitude hunter-gatherers are available (e.g., Constandse-Westermann 1993;Robert-Lamblin 2006). In general, hunter-gatherers are strongly dependent on key resources, and their demographic fate tracks that of their primary prey (Morin 2008;Stenton 1991) (Figure 1). Importantly, these fl uctuations are not merely seasonal, nor are they caused by hunting pressure exerted by humans (Aanes et al 2000;Kojola 2006, 2008).…”
Section: Hunter-gatherer Demography and Climate Changementioning
confidence: 99%
See 2 more Smart Citations
“…It is known that human population size in Europe declined from the beginning of the Upper Paleolithic until the Bølling-Allerød interstadial, because of a dietary breadth contraction caused by prey extinction. 15 A likely effect of this would have been an enhancement of genetic drift coupled with recurrent population bottlenecks, which are the major factors in the shaping of genetic diversity. 16 During the Last Glacial Maximum, conditions would have been worsened, as paleoecological modeling has shown the maximum range of the glacial refuges to be small and constrained by permafrost areas.…”
Section: Introductionmentioning
confidence: 99%